2019
DOI: 10.3390/coatings9090551
|View full text |Cite
|
Sign up to set email alerts
|

Surface Stoichiometry and Optical Properties of Cux–TiyCz Thin Films Deposited by Magnetron Sputtering

Abstract: Ternary carbide in metal matrix composites constitute a big challenge in the industry, and in this regard their surface treatment is one of the most important issues. Ternary carbide (CuxTiyCz, where x, y and z are integers) thin films are synthesized by magnetron sputtering and characterized with respect to the film depth. X-ray photoelectron spectroscopy (XPS) of Cu-2p and Ti-2p peaks shows the associated shake-up satellite peaks at a smaller film depth; the peak intensity is reduced at a higher depth. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…So it can be concluded that for optimum conductivity, the C content should not exceed more than 50%. The evaluation of band-gap of Cu-TiC thin film is already reported in the range between 1.83 eV to 2.2 eV [10]. The inclusion of Cu with TiC phase has formed a film with band-gap close to that of a semiconductor.…”
Section: Xrd Analysismentioning
confidence: 96%
See 1 more Smart Citation
“…So it can be concluded that for optimum conductivity, the C content should not exceed more than 50%. The evaluation of band-gap of Cu-TiC thin film is already reported in the range between 1.83 eV to 2.2 eV [10]. The inclusion of Cu with TiC phase has formed a film with band-gap close to that of a semiconductor.…”
Section: Xrd Analysismentioning
confidence: 96%
“…The synthesis of Cu-TiC composites is mostly performed by following self-propagating high-temperature synthesis [1,9], DC/HiPIMS magnetron sputtering system [10], microwave processing [11] or powder metallurgy [2,9,12] involving mostly mechanical ball milling [13,14] and infiltration technique [3]. Earlier it has been reported that TiC x with different values of x, can directly influence the distribution of carbides in TiC stoichiometry of Cu-TiC composites [9].…”
Section: Introductionmentioning
confidence: 99%
“…The left subpeaks (green lines) observed at 934.5 and 954.3 eV are characteristic of the Cu 2+ , while the right subpeaks (blue lines) observed at 932.5 and 952.4 eV can be attributed to the Cu + , which are reduced from a fraction of Cu 2+ . Furthermore, two accompanying shakeup satellite peaks corroborated the presence of a coordination interaction in the form of Cu 2+ . The similarly divided subpeaks of Cu 2p suggested their electronic similarities.…”
Section: Results and Discussionmentioning
confidence: 79%
“…41 Furthermore, two accompanying shakeup satellite peaks corroborated the presence of a coordination interaction in the form of Cu 2+ . 42 The similarly divided subpeaks of Cu 2p suggested their electronic similarities. However, as shown in Figure S10, no Zn 2p was detected in the M 4+ and Zn 2+ co-blended MM-MON films, resulting from the fast dissolution of Zn 2+ due to the weakest and a relatively longer Zn−O bond (Table S4), thus bearing the worst coordination ability.…”
Section: Resultsmentioning
confidence: 95%
“…In this way, the electron density of the carbon atom decreases, causing the BE to drop from 288.77 to 288.43 eV. The low-resolution spectra for copper are presented in Figure S2 in Supplementary, evidencing the predominance of Cu(II) species in the alginate beads based on the peaks that correspond to Cu 2p2/3, and Cu 2p1/2 [ 58 , 59 , 60 , 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%